Hormone Replacement Therapy after Unilateral Adrenalectomy - Parfentiev, R.; Kryzhanovskyi, Yu.; Sliepov, V.; Vododyuk, V.; Parfentieva , N. (Journal of Education, Health and Sport, 2025)
Unilateral adrenalectomy is widely performed for the treatment of both hormonally active and inactive adrenal tumors; however, the need for postoperative hormone replacement therapy (HRT) remains controversial. This study aimed to evaluate the necessity, duration, and clinical relevance of glucocorticoid replacement after unilateral adrenalectomy based on functional recovery of the hypothalamic–pituitary–adrenal (HPA) axis. A prospective cohort study with elements of retrospective analysis included 108 patients who underwent minimally invasive unilateral adrenalectomy between 2018 and 2025. Hormonal status was assessed preoperatively, in the early postoperative period, and at 1, 3, and 6 months after surgery. Morning serum cortisol, ACTH, and electrolytes were measured, with dynamic testing performed when indicated. Glucocorticoid replacement therapy was prescribed individually based on laboratory results and clinical presentation. Glucocorticoid replacement therapy was required in 46 patients (42.6%) in the early postoperative period, while 62 patients (57.4%) maintained adequate cortisol levels without replacement. The need for HRT was strongly associated with tumor functional status: replacement therapy was necessary in 84.6% of patients with corticosteromas, 50.0% with aldosteromas, and 42.9% with pheochromocytomas, compared with only 22.2% of patients with hormonally inactive tumors. In most cases, HRT was transient, with normalization of morning cortisol allowing discontinuation of therapy in 37.0% of patients at 1 month, 63.0% at 3 months, and 82.6% at 6 months. Persistent adrenal insufficiency beyond 6 months occurred in only 7.4% of the total cohort and exclusively among patients with hormonally active tumors. The study demonstrates that routine hormone replacement therapy after unilateral adrenalectomy is not universally required. Instead, individualized management based on systematic hormonal monitoring allows safe prevention of adrenal insufficiency while avoiding unnecessary long-term glucocorticoid exposure, thereby optimizing postoperative outcomes and patient quality of life